THE EFFECT OF RESEARCH ON RICE PRODUCTION IN PHILIPPINE - Singh, Baljinder; Singh, Gurdeep (International Journal of Psychosocial Rehabilitation, 2021)
Research and development have a significant impact on rice production in the Philippines. Rice creation development in the Philippines from 1996 to 2007 was analyzed utilizing a summed-up instrumental variable assessor and a translog creation work assessment. A creation system was utilized to look at how traditional and non-ordinary contributions, alongside lingering all-out factor efficiency, added to the expansion in by and large creation volume. Between 2001-2006 and 2002-2007, yield developed seriously during the stormy and dry seasons, contrasted with 1996-2001 and 1997-2002, when results expanded less. Utilizing water systems, crossbreed and third-era present-day innate assortments, rice creation instructional meetings, excellent seed, and machine proprietorship were viewed as the most important non-traditional inputs in these periods, according to the findings.